2017
DOI: 10.1108/ecam-01-2016-0006
|View full text |Cite
|
Sign up to set email alerts
|

Value conflicts and organizational commitment of internal construction stakeholders

Abstract: Purpose The possible effect of conflicts as the consequence of differences between personal and organizational values (OV) on organizational commitment (OC) of internal construction stakeholders was an unclear issue in the areas of organizational behaviour in the construction industry, especially in Malaysia. Therefore, the purpose of this paper is to focus on this issue in the Malaysian construction industry. Design/methodology/approach This paper targeted professional project consultants, who are identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…The findings indicated a high level of value conflicts in the construction organizations, which significantly and negatively affected the commitment of the internal stakeholders in the Malaysian construction industry. Again, even if the Sarawak state was included in their data collection, the focus and scope of Panahi et al [6] work differ from the current study. Due to the research gap identified in the literature, the current research aims to identify the causes of construction-related conflict among construction workers in the eastern region of Malaysia.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…The findings indicated a high level of value conflicts in the construction organizations, which significantly and negatively affected the commitment of the internal stakeholders in the Malaysian construction industry. Again, even if the Sarawak state was included in their data collection, the focus and scope of Panahi et al [6] work differ from the current study. Due to the research gap identified in the literature, the current research aims to identify the causes of construction-related conflict among construction workers in the eastern region of Malaysia.…”
Section: Introductionmentioning
confidence: 68%
“…Although Ling and Khoo's [5] work also relates to the harmonization of relational conflict, their research differs from this current research in terms of focus and scope. Panahi et al [6] examined the impact of conflict on the organizational commitment of internal construction stakeholders in the Malaysian construction industry. The findings indicated a high level of value conflicts in the construction organizations, which significantly and negatively affected the commitment of the internal stakeholders in the Malaysian construction industry.…”
Section: Introductionmentioning
confidence: 99%
“…These are related to Project Characteristics explained under the project setup. Other types of value include personal vs. organizational value, where perceived value shall be considered both at the personal level and at the organizational commitment level (Panahi et al 2017).…”
Section: A the Value Conceptmentioning
confidence: 99%
“…Value is seen as an ambiguous term and it is still not well communicated (Salvatierra-Garrido et al 2012). Moreover, value conflicts are found to be high in construction organizations leading to low commitment from internal stakeholders (Panahi et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There are seven past researches in the period between years 2013-2017 that are related to the employee retention factors. The findings can be categorised into job satisfaction [4][5][6][7][8][9] and organisational commitments [7][8][9][10]. The employees' feelings towards performing the job are measured as satisfaction whether in positive or negative perspectives [11] which can give impacts to the employees' productivity and performance [7].…”
Section: Past Researchesmentioning
confidence: 99%